Problem-Based Learning (PBL) Model and Learning Motivation In Improving Writing Skills of Elementary School Students - Alami Fitria; Elfia Sukma; Adrias; Ulfia Rahmi; Syahrul Ramadhan; Trinindi Eriswan Fitri (Jurnal Ilmiah Sekolah Dasar, 2025)
Technological advancement has reduced writing skills due to dependence on the internet, AI, and ChatGPT. This study aims to examine the effect of Problem-Based Learning (PBL) and learning motivation on elementary students’ writing skills. This study uses a quantitative research method using a quasi-experimental design. The population of this study was all 165 sixth-grade elementary school students. The sample selection in this study used a non-probability sampling technique with a sample size of 37 students. The data collection method used questionnaires and tests. The instruments used in this study were learning motivation questionnaires and tests. The technique used to analyze the data was inferential statistics. The results of this study indicate that the Problem-Based Learning (PBL) learning model has a significant effect on elementary school students' writing skills. The experimental group outperformed the control group in explanatory writing skills (p = 0.004 < 0.05). Highly motivated students in the experimental class achieved higher scores than those in the control class. Learning motivation also had a significant effect on writing skills (p = 0.029 < 0.05). It is concluded that PBL and learning motivation improve students’ writing skills.